Dairy product consumption and risk of colorectal cancer in an older mediterranean population at high cardiovascular risk. Issue 6 (4th May 2018) - Barrubés, Laura; Babio, Nancy; Mena‐Sánchez, Guillermo; Toledo, Estefania; Ramírez‐Sabio, Judith B.; Estruch, Ramón; Ros, Emilio; Fitó, Montserrat; Arós, Fernando; Fiol, Miquel; Santos‐Lozano, José Manuel; Serra‐Majem, Lluís; et al.
Abstract : Prospective studies have reported an inverse association between the consumption of total dairy products and milk and the risk of colorectal cancer (CRC). Nonetheless, there is little and inconsistent evidence regarding subtypes of dairy product and CRC risk. We assessed the associations between the consumption of total dairy products, their different subtypes and CRC risk in older Mediterranean individuals at high cardiovascular risk. We analyzed data from 7, 216 men and women (55–80 years) without CRC at baseline from the PREvención con DIeta MEDiterránea study. Individuals were recruited between 2003 and 2009 and followed up until December 2012. At baseline and yearly thereafter, consumption of total and specific dairy products was assessed using a validated 137‐item food‐frequency questionnaire. Cox proportional hazards ratios (HRs) of CRC incidence were estimated for tertiles of mean consumption of dairy products during the follow‐up. During a median [interquartile range] follow‐up of 6.0 [4.4–7.3] years, we documented 101 incident CRC cases. In the multivariable‐adjusted models, HRs and 95% confidence intervals (CIs) of CRC for the comparison of extreme tertiles of total dairy product and low‐fat milk consumption were 0.55 (95% CI: 0.31–0.99; p ‐trend = 0.037) and 0.54 (95% CI: 0.32–0.92; p ‐trend = 0.022), respectively. No significant associations with other dairy products (whole‐fat and low‐fat dairy products; total, low‐fat and whole‐fat yogurt; cheese; total, low‐fat and whole‐fat milk; concentrated full‐fat dairy products, sugar‐enriched dairy products and fermented dairy products) were found. A high consumption of total dairy products and low‐fat milk was significantly associated with a reduced CRC risk. Abstract : What's new? Relative to other aspects of the Mediterranean diet, such as the intake of alcohol and processed meats, little is known about the relationship between the consumption of dairy products or their fat content and colorectal cancer (CRC) risk. Here, potential relationships were assessed among older Mediterranean individuals at high risk of cardiovascular disease. The data suggest that CRC incidence is inversely related to high total dairy product consumption. Of particular importance was the intake of low‐fat milk, which was the primary driver behind the inverse association. Other dairy products were not significantly associated with CRC risk.